DEVELOPING A QUALITY STANDARDS OF PROGRAMS AND SERVICES OF TALENTED STUDENTS TABUK CITY SCHOOLS IN LIGHT OF INTERNATIONAL STANDARDS - Khaled Arab, Mazhoud Saeed Alshamrani, Saud Saleh Alenzi, Faisal Saud Albalawi, Roa Mohamed Abushaira (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aimed to develop standards for the quality of services and programs for gifted students in Tabuk schools in the light of international standards. (90) individuals who deal with gifted students permanently and directly (teacher, official or supervisor in the field, and a parent) participated in the study. To achieve the aims of the study; A questionnaire has been developed to measure the degree of availability and degree of importance of quality standards for gifted students’ services and programs in Tabuk city schools, consisting of (30) items distributed equally into three areas: The first dimension: planning and organization, the second dimension: curricula and education The third dimension: professional development and creativity environment, and indications were extracted The sincerity and firmness are acceptable to her. The results of the study showed that the degree of availability of quality standards for gifted students ’services and programs in Tabuk city schools was medium, while the degree of importance of quality standards for gifted students’ services and programs in Tabuk city schools was high, and as for the sub-dimensions regarding the degree of availability, the planning and organizing dimension came in the rank. The first is followed by the dimension related to curricula and education, and in the last rank came the dimension related to professional development and the creativity environment, and for the sub dimensions with regard to the degree of importance, the dimension related to planning and organization came in the first rank, followed by the dimension related to curricula and education and in the last rank came the dimension related to professional development and creativity environment